Taiwan’s Halal Culinary Gastrodiplomacy in Rural Java: Survival Strategies of Former Indonesian Migrant Workers - Bayu Mitra A. Kusuma; Theresia Octastefani (UIN Siber Syekh Nurjati Cirebon, 2026)
The repatriation of Indonesian Migrant Workers (IMWs) does not merely generate economic challenges but also produces new socio-cultural dynamics of livelihood survival. One emerging strategy is to use culinary experiences acquired in Taiwan as the foundation for micro-enterprises in rural Java. Nevertheless, former IMWs are required to undertake adaptation and modification processes to construct a halal image for Taiwanese cuisine. In this context, halal Taiwanese cuisine functions not only as an economic commodity but also as an instrument of gastrodiplomacy that negotiates identity, market preferences, and socio-religious legitimacy at the local level. This study employs a qualitative case study design in Banyuwangi, a region recognized as a concentration area for former IMWs. Data were collected through participatory observation, in-depth interviews, and documentation related to halal Taiwanese culinary activities operated by former IMWs. The findings reveal that: first, the success of halal Taiwanese culinary enterprises in Banyuwangi is strongly determined by their capacity to adapt to local tastes and community needs; second, these enterprises contribute to the strengthening of five livelihood capitals of former IMWs, namely human, social, financial, physical, and natural capital; and third, gastrodiplomacy operates as an intangible livelihood asset that transforms migration experience into social legitimacy and economic sustainability for former IMWs.